Broken Sacral Neuromodulation Lead Migration Into the Sigmoid Colon: A Case Report. Issue 6 (November 2018) - Shannon, Megan B.; Gupta, Neil; Eberhardt, Joshua; Farooq, Ahmer V.
Abstract : Abstract: Sacral neuromodulation is an effective treatment of urinary incontinence, fecal incontinence, and idiopathic urinary retention. The procedure is considered low risk with overall low complication rates. This report describes a 40-year-old woman who underwent sacral neuromodulation explant and full-system implant for weaning efficacy of her device. During device removal, the tined lead broke and was left in situ. Four months later, she was diagnosed as having a wound infection at the site of the retained lead. Imaging revealed lead fragment migration into the sigmoid colon. A colocutaneous fistula was noted soon thereafter. The retained lead was removed during a colonoscopy and the fistula healed. A retained lead can result in migration through the peritoneum and into the colon. This can be managed with assistance from colorectal or gastroenterology consultants.